PENGEMBANGAN MODUL PADA MATA DIKLAT MENGELOLA PERTEMUAN ATAU RAPAT DI SMK NEGERI 10 SURABAYA - JADIDAH, NUR (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2013)
ABSTRACT Good materials teaching would be push and influence the students' interest to develop curious on materials learning. Therefore, the development of the modules should be presented in an innovative way, exciting, according to the basic competency requirements, straightforward language, and be able to stimulate student mindset and understanding. This development module has important when the government continues to implement Educational Unit Level Curriculum (KTSP) policy to develop standards unit for improve education system. This study aims to develop teaching materials module. The research object is the class X at SMK Negeri 10 Surabaya. The subject were 15 students in the class X. 4-D approach or also known as define, design, develop and disseminate used to compile this module development step. Assessment of the quality of the module done by expert reviewers with three aspects rated to wit language aspect, material modules aspect and module design aspect. Expert validation study results and showed as good judgment on the feasibility of the developed module. Quality assessment of the feasibility has score grade 63% in module language judgment or as strong quality category. Feasibility content has scores 54% or moderate, reaching 72% score grade for material presenting, and in design powerful and reaches 92% or quality superior. Feasibility of the overall total for the module reaches the level of 70% score or have a strong eligibility criteria. Tests on student assessment also provides a very good responseconclusion with a total score reaches 81%. The powerful assessment includes assessing the physical aspect of teaching materials and teaching materials each scored 81%. Keywords: module, Instructional Materials, Secretariat, Meetings, Conferences.